2020
DOI: 10.2147/cmar.s287682
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Analysis of the Diagnosis and Treatment of Fetal Sacrococcygeal Teratomas

Abstract: Objective The present study aims to discuss the clinical features, treatment, and prognosis of fetal sacrococcygeal teratomas (SCTs) to improve the standard of diagnosis and treatment. Methods The clinical data of 15 pregnant females with fetal SCT, admitted to Fujian  Maternity and Child Health Hospital from January 2013 to January 2020, were retrospectively analyzed with respect to clinical characteristics, imaging features, complications, treatment options, and pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Those presenting in older infants tend to have a higher malignant potential and those presenting in utero have a poor prognosis due to complications. It has been reported that fetal mortality is higher if the gestational week at the time of diagnosis is early in SCT [ 18 ]. Mass size, the solid component, and the vascularity of the mass are reported to be more important on prognosis than the gestational age at the time of diagnosis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those presenting in older infants tend to have a higher malignant potential and those presenting in utero have a poor prognosis due to complications. It has been reported that fetal mortality is higher if the gestational week at the time of diagnosis is early in SCT [ 18 ]. Mass size, the solid component, and the vascularity of the mass are reported to be more important on prognosis than the gestational age at the time of diagnosis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that fetal mortality is higher if the gestational week at the time of diagnosis is early in SCT [ 18 ]. Mass size, the solid component, and the vascularity of the mass are reported to be more important on prognosis than the gestational age at the time of diagnosis [ 18 ]. The prognosis of SCTs detected in the prenatal period is to be worse than those detected in the neonatal period which may be due to the fact that larger tumors are more likely to be detected in fetal life, and tumors detected in early pregnancy have greater growth potential [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The selection of articles required the English and French languages, clinical trials, case presentations, and case series. In total, 39 published articles were identified according to the inclusion criteria and are presented in Table 5 [3,5,10,11,13,18,19,21,22,24,25]. Following the analysis of the series of 226 cases with immature SCT, 19 G1, 29 G2, and 50 G3 were identified according to the Gonzales-Crussi classification, and 9 TI, 12 TII, 5 TIII, and 1 TIV cases according to the Altman classification; for the other cases, no data were available.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Teratomas are considered rare fetal tumors, with an incidence varying between 1.3 and 2.2 in 1000 pregnancies, derived from the three germ layers [1]. Since 1975, when Santos-Ramos and Duenhoelter [2] described sonographically sacrococcygeal teratoma (SCT), the imaging technology of the prenatal diagnosis of this malformation has been continuously improved, this being highlighted by the increase in the detection rate from 50% in 2008 [3,4] to 100% in 2020 [5]. SCTs are the most common congenital tumors, arising from the multipotential cells of Hensen's node towards the end of the second week and the beginning of the third week of gestation [6].…”
Section: Introductionmentioning
confidence: 99%
“…SCT can be detected on ultrasound as early as the first trimester, presenting as a large mass originating from the sacrococcygeal area, with or without an intrapelvic component [ 6 ], [ 7 ]. It is recommended to perform serial ultrasonography, including Doppler ultrasonography, to monitor the tumor’s growth and vascularization over time.…”
Section: Diagnosticsmentioning
confidence: 99%